2019
DOI: 10.1038/s41598-019-45234-8
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Brain Injury-related voiding dysfunction in mice is caused by damage to rostral pathways, altering inputs to the reflex pathways

Abstract: Brain degeneration, including that caused by traumatic brain injury (tBI) often leads to severe bladder dysfunction, including incontinence and lower urinary tract symptoms; with the causes remaining unknown. Male C57BL/6J mice underwent repetitive moderate brain injury (rmdTBI) or sham injury, then mice received either cis p-tau monoclonal antibody (cis mAb), which prevents brain degeneration in TBI mice, or control (IgG). Void spot assays revealed age-dependent incontinence in IgG controls 8 months after inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 84 publications
(117 reference statements)
2
16
0
Order By: Relevance
“…Differences often occur in the duration and time between impacts across different models 110 . Importantly, many models also observe the long-term effects post injury, an important factor in trying to replicate CTE as a neuropathology [111][112][113] . Because of the similarity in the results of these established models, more research is needed to determine what factors induce pathological changes, including the type of mechanical force, injury frequency, and severity of injury.…”
Section: Relevance Of Pre-clinical Models Of Tbi To Human Ctementioning
confidence: 99%
“…Differences often occur in the duration and time between impacts across different models 110 . Importantly, many models also observe the long-term effects post injury, an important factor in trying to replicate CTE as a neuropathology [111][112][113] . Because of the similarity in the results of these established models, more research is needed to determine what factors induce pathological changes, including the type of mechanical force, injury frequency, and severity of injury.…”
Section: Relevance Of Pre-clinical Models Of Tbi To Human Ctementioning
confidence: 99%
“…In the present study, results indicated that the RV was remarkably and significantly increased in TBI rats compared to that of NC rats. The PMC plays a crucial role in bladder inhibitory actions [8], and when this center is no longer intact, detrusor hyperreflexia occurs. Two PMCs are respectively responsible for bladder contractions and relaxation, which have reciprocal inhibitory effects.…”
Section: Discussionmentioning
confidence: 99%
“…In the acute stage of TBI, the common cognitive outcomes are decreased speed of information processing, attention problems, and confusion and in the chronic stage the outcomes extend to dizziness, sleep disturbance, anxiety, and depression. This chronic condition leads to the risky state of post-concussive syndrome [7,8]. Numerous methods are used to analyze outcomes of a TBI such as the fluid percussion model [9], weight-drop model (WDM) [10], controlled cortical-impact (CCI) model [11], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Males are more susceptible to TBI consequences than females (Taylor et al, 2017), and in light of previous research (Albayram et al, 2017; Albayram et al, 2019; Guilhaume‐Correa et al, 2020; Kondo et al, 2015; Kondo, et al, 2015; Taylor et al, 2017; Xiong et al, 2013), we focused on adult male animals to obtain more thoughtful results. The animals were housed and cared for according to the protocol approved by the Royan Institutional Animal Care and Ethical Committee (IR.ACECR.ROYAN.REC.1397.233) in conformity with the National Institute of Health (NIH) Guide for the Care and Use of Laboratory Animals.…”
Section: Methodsmentioning
confidence: 99%